Abigail, Ruth and the Case for Female Biblical Authorship - Verman, Mark (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
Until a century ago it was generally assumed that all of the books of the Tanakh were written by men, primarily for men. Herein the author will survey the growing number of scholars, female and male, who have contemplated the possibility that some of these works were composed by women. One of the principal texts that is commonly highlighted is Ruth. Although candidates for its authorship have seldom been suggested, it will be demonstrated herein that Abigail is worthy of consideration as the originator of the story of Ruth.